Palladium‐Catalyzed Remote δ‐C−H Selenylation of Arylethylamide and Alkenylethylamide Derivatives. Issue 20 (20th September 2022) - Ma, Wenbo; Zhou, Yunhao; Wang, Yang; Li, Bo; Zheng, Tao; Cheng, Zemin; Mei, Ruhuai
Abstract: A palladium‐catalyzed remote δ ‐C−H selenylation of arylethylamide derivatives with readily available diselenides has been reported. This protocol relies on the use of a removable picolinamide directing group to access unsymmetrical diaryl selenides in 45–98% yields. Furthermore, the inactivated δ ‐C(alkenyl)−H bond was also compatible in this reaction and afforded the thermo‐dynamically unfavorable Z ‐selective‐alkenyl selenides with complete control of site‐ and stereoselectivity. Abstract :